Facilities and services in Universiti Malaysia Sabah: preliminary findings from the perspectives of students with disabilities - Muhammad Idris Bullare @ Bahari; Alfred Chan Huan Zhi; Adeymend Reny Japil; Mohd. Dahlan A. Malek; Lailawati Madlan @ Endalan; Norsimah Dasan; Ida Shafinaz Mohamed Kamil; Nur Farhana Ardillah Aftar; Wan Anor Wan Sulaiman; Noor Hassline Mohamed; Kenson Rubanjar; Hajah Siti Rafidah Binti Haji Md Said (Georgian Technical University, 2021)
The current study investigates the challenges and barriers of facilities and services for students with disabilities (SWDs) in Universiti Malaysia Sabah. This study used a grounded theory approach. This research had nine respondents participated (two male and seven female students). Data in this investigation were collected using in-depth interviews and focus-group discussions and analysed with qualitative content analysis. Four critical challenges and barriers of facilities and services faced by SWDs in Universiti Malaysia Sabah were discovered as follows: a) accessibility, b) facility, c) student management, and d) mobility. This input may contribute to developing and improving facilities and services for SWDs in Universiti Malaysia Sabah.